PEMANFAATAN KEUANGAN SUBAK DALAM MENINGKATKAN PRODUKTIVITAS PERTANIAN DI DESA MANIKLIYU, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Mahadewi, Kadek Julia (Universitas Islam Syekh Yusuf Tangerang, 2021)
The existence of subak has an important role in empowering agriculture and the welfare of farmers. Manikliyu Village, Kintamani District, Bangli Regency is the area of ​​the majority of the community with livelihoods as farmers through agricultural development through Subak Ulun Suwih. The problem faced is the lack of direct use of subak financial funds to farmers in an effort to increase agricultural productivity. This activity is carried out using the observation method of interviews, discussions, and socialization of the delivery of ideas to subak parties related to the use of subak financial funds for farmers. This community service activity aims to examine the problems that occur. In this community service activity resulted in the purchase of Arabica coffee plant seeds which were given to farmers through the allocation of financial funds from Subak Ulun Suwih. Keywords: Financial Utilization, Increase, Agricultural Productivity